Impacts of climate change on water fluxes and soybean growth in southern Brazil - Silva Moreira, Virnei; Antonio Candido, Luiz; Crestani Mota, Marcelo; Webler, Geovane; do Prado Oliveira, Elisangela; Regina Roberti, Debora (Revista Ciência Agronômica, 2022)
This study aims to analyze the consequences of climatic change in the water dynamic and growth soybean in Southern Brazil. Scenarios were created for conditions of a 2 ºC temperature increase, a 20% reduction, and a 50% increase in precipitation rates, representing hot, dry and wet scenarios, respectively. The atmospheric forcing generated were used as input data for the agricultural version of the Integrated Biosphere Simulator model (Agro-IBIS) and simulations were carried out for a soybean growing season in the northwestern Rio Grande do Sul, Brazil. The following variables estimated by Agro-IBIS were analyzed: soil moisture, soybean leaf area index (LAI), evaporation, and transpiration. The results showed that the climatic changes projected by the simulations influence soybean growth in the study area. By increasing the temperature in 2 °C, the Agro-IBIS model indicated the occurrence of shorter crop growth cycles and even more impactful results on the leaf area index, with a 70% reduction in the highest values. Furthermore, a 50% increase in precipitation rate showed positive effects on agriculture, indicated by increased LAI in the reproductive period. On the other hand, a 20% reduction in precipitation has a negative effect, as it exposes the crop to water deficit conditions, impacting soil moisture and decreasing LAI. The soil evaporation is also intensified with increased temperatures due to the higher evaporative demand of the atmosphere and a significant decline in LAI. The transpiration for the hot scenario is more strongly impacted during the vegetative growth stage and leaf senescence.